The Malaysian real trade balance and the real exchange rate - Yusoff, Mohammed (Taylor & Francis, 2007)
The cointegration technique is used to examine the long-run and short-run relationships between the real Malaysian trade balance with the real exchange rate, domestic and world incomes. The results suggest that a real ringgit exchange rate depreciation improves the trade balance in the long run. World and domestic incomes are also found to be important determinants of trade balance. The significance of world income on trade balance indicates that Malaysia is prone to external shocks. An error-correction model is then estimated to study the short-run dynamics of the effects of exchange rate. The impulse response analysis shows that the effect of exchange rate on the trade balance lasts for about three years. A devaluation of ringgit will initially improve the trade balance, albeit small,after which the trade balance starts to deteriorate, and then improves again suggesting that there exists a delayed J-curve.